The lean strategy : using lean to create competitive advantage, unleash innovation, and deliver sustainable growth - Ballé, Michael, 1965-; Jones, Daniel T.; Chaize, Jacques; Fiume, Orest J. (McGraw-Hill Audio, 2018)
A lean strategy is about gaining a competitive edge by offering better quality products at competitive prices and making a sustainable profit by eliminating waste through engaging employees in discovering deeper ways to think about their own jobs and smarter ways of working together. In its current form, lean has been radically effective, but its true powers have yet to be harnessed.